Cancer cachexia as a multiorgan failure: Reconstruction of the crime scene - Ferrara, Michele; Samaden, Maria; Ruggieri, Elena; Vénéreau, Emilie (Frontiers in Cell and Developmental Biology, 2022)
Cachexia is a devastating syndrome associated with the end-stage of several diseases, including cancer, and characterized by body weight loss and severe muscle and adipose tissue wasting. Although different cancer types are affected to diverse extents by cachexia, about 80% of all cancer patients experience this comorbidity, which highly reduces quality of life and response to therapy, and worsens prognosis, accounting for more than 25% of all cancer deaths. Cachexia represents an urgent medical need because, despite several molecular mechanisms have been identified, no effective therapy is currently available for this devastating syndrome. Most studies focus on skeletal muscle, which is indeed the main affected and clinically relevant organ, but cancer cachexia is characterized by a multiorgan failure. In this mini-review, we focus on the current knowledge on the multiple tissues affected by cachexia and the biomarkers with the attempt to define a chronological pathway, which might be useful for the early identification of patients who will undergo cachexia. Indeed, it is likely that the inefficiency of current therapies might be attributed, at least in part, to their administration in patients at the late stages of cachexia.